HIV-1 R5 Macrophage-Tropic Envelope Glycoprotein Trimers Bind CD4 with High Affinity, while the CD4 Binding Site on Non-macrophage-tropic, T-Tropic R5 Envelopes Is Occluded - Quitadamo, Briana; Peters, Paul J.; Repik, Alexander; O¿Connell, Olivia; Mou, Zhongming; Koch, Matthew; Somasundaran, Mohan; Brody, Robin; Luzuriaga, Katherine; Wallace, Aaron; Wang, Shixia; Lu, Shan; et al. (ASM, 2018)
HIV-1 R5 variants exploit CCR5 as a coreceptor to infect both T cells and macrophages. R5 viruses that are transmitted or derived from immune tissue and peripheral blood are mainly inefficient at mediating infection of macrophages. In contrast, highly macrophage-tropic (mac-tropic) R5 viruses predominate in brain tissue and can be detected in cerebrospinal fluid but are infrequent in immune tissue or blood even in late disease. These mac-tropic R5 variants carry envelope glycoproteins (Envs) adapted to exploit low levels of CD4 on macrophages to induce infection. However, it is unclear whether this adaptation is conferred by an increased affinity of the Env trimer for CD4 or is mediated by postbinding structural rearrangements in the trimer that enhance the exposure of the coreceptor binding site and facilitate events leading to fusion and virus entry. In this study, we investigated CD4 binding to mac-tropic and non-mac-tropic Env trimers and showed that CD4-IgG binds efficiently to mac-tropic R5 Env trimers, while binding to non-mac-tropic trimers was undetectable. Our data indicated that the CD4 binding site (CD4bs) is highly occluded on Env trimers of non-mac-tropic R5 viruses. Such viruses may therefore infect T cells via viral synapses where Env and CD4 become highly concentrated. This environment will enable high-avidity interactions that overcome extremely low Env-CD4 affinities.